Defining tafoni: Re-examining terminological ambiguity for cavernous rock decay phenomena. (December 2015) - Groom, Kaelin M.; Allen, Casey D.; Mol, Lisa; Paradise, Thomas R.; Hall, Kevin
Cavernous rock decay processes represent a global phenomenon, ubiquitous to all environments, with the viewable-in-landscape form usually being the final descriptor (e.g. "alveoli"), sometimes alluding to the specific decay process (e.g. "pitting"), other times not (e.g. "honeycombing"). Yet, definitive terminology remains inconsistent, usually owing to variability in dimension, morphometry, distribution, and/or academic lineage. This lack of an established lexicon limits scientific collaboration and can generate scientific bias. With no official consensus on appropriate distinctions, researchers and scientists must either be familiar with all the possible terminology, or know the apparent distinction between "forms"—which can seem arbitrary and, even more frustrating, often differs from researcher to researcher, scientist to scientist. This article reviews the historical and contemporary progression of scientific inquiry into this decay—and, arguably, erosional—feature to identify lexical inconsistencies and promote a singular unifying term for future scholars. Ultimately, the authors support using "tafoni" (singular: "tafone") as the non-scalar universal term—the form created by numerous processes involved in cavernous decay features—and strongly suggest researchers adopt the same vernacular in order to promote collaboration.